Conservative reconstruction of the smile by orthodontic, bleaching, and restorative procedures - Sundfeld, Renato Herman; Machado, Lucas Silveira; de Oliveira, Fernanda Garcia; Santos, Eduardo Almada; Lugato, Isabel Cristina Prado Torres; Neto, Daniel Sundfeld (European Journal of Dentistry, 2012)
The following is a clinical case report of a patient whose chief complaint was the presence of generalized spacing in the maxillary anterior segment following orthodontic treatment. After meticulous clinical analyses and discussions of the clinical procedures to be adopted, dental bleaching was performed in both arches with 10% hydrogen peroxide (Opalescence Trèswhite Supreme 10% Hydrogen Peroxide - Ultradent Products, Inc., South Jordan, USA) after the conclusion and stabilization of orthodontic treatment. Then, the orthodontic appliance was removed and the diastemas in the maxillary anterior teeth were closed with Amelogen Plus (Ultradent Products, Inc., South Jordan, USA) resin composite. It was observed that the association of orthodontic, bleaching, and restorative procedures was capable of restoring dental shape, function, and esthetics, allowing the patient to smile without hesitation. (Eur J Dent 2012;6:105-109)
Keywords: Orthodontics; diastema; dental bleaching; composite resin